Integrated PjBL-STEAM Learning with ESD to Improve Students' Critical Reasoning in Renewable Energy: Bibliometric Analysis - Reny Yuliyanti; Bambang Subali; Ani Rusilowati (Borneo Research and Education Center, 2025)
This study aims to map and analyze the development of research on the development of integrated digital teaching materials, PjBL-STEAM, with an ESD framework to improve students' critical reasoning skills on renewable energy materials through bibliometric analysis. Data were obtained from the Scopus database and selected using certain criteria, resulting in 329 articles published from 2012 to 2025. The analysis was conducted using Bibliometrix software to examine publication trends, the most productive journals, the most contributing authors and countries, and thematic evolution. The synthesis results show that the STEAM approach has proven effective in developing students' critical thinking, creativity, and collaboration skills. However, an explicit ESD integration framework in open-ended high school physics materials is still limited. Furthermore, research that simultaneously integrates PjBL, STEAM, and Education for Sustainable Development on renewable energy materials is still rare. These findings indicate a research opportunity to develop integrated digital teaching materials, PjBL-STEAM, with an ESD framework specifically designed to improve students' critical reasoning skills.